Analisis Tindak Tutur Asertif dalam Praktik Pembelajaran Teks Negosiasi pada Siswa Kelas X dan Impilkasinya terhadap Kemampuan Berpikir Analitis - Karuniawan, Dwiky Yoga (Fakultas Bahasa dan Sastra Universitas PGRI Kanjuruhan Malang, 2025)
This study aims to explore the forms of assertive speech acts in the practice of negotiation text learning among students and to describe the implications of assertive speech acts in the negotiation text learning process for the analytical thinking skills of Grade X students. This research employs a descriptive qualitative method, chosen for its relevance in providing an in-depth depiction of the assertive speech acts that emerge during the learning of negotiation texts and in examining their implications for students' analytical thinking abilities. The data source in this study consists of verbal utterances produced by students during the negotiation text learning process with the theme of healthy food in class X-12 at Senior High School of 7 Kediri. Data collection was conducted using documentation and observation-note-taking techniques. The findings of this study reveal 31 forms of assertive speech acts in the negotiation text learning practice themed around healthy food among class X-12 students at SMAN 7 Kediri, namely: a) informing (9), b) pointing out (7), c) suggesting (5), and d) delivering (11). The focus of this research is on five student groups from class X-12 at Senior High School of 7 Kediri who carried out negotiation text practices at the front and back school canteens.